Acetylcholinesterase inhibition: a novel approach in the treatment of neurogenic orthostatic hypotension. Issue 9 (21st August 2003) - Singer, W; Opfer-Gehrking, T L; McPhee, B R; Hilz, M J; Bharucha, A E; Low, P A
Abstract : Background: Pharmacological treatment of orthostatic hypotension is often limited because of troublesome supine hypertension. Objective: To investigate a novel approach to treatment using acetylcholinesterase inhibition, based on the theory that enhanced sympathetic ganglion transmission increases systemic resistance in proportion to orthostatic needs. Design: Prospective open label single dose trial. Material: 15 patients with neurogenic orthostatic hypotension caused by: multiple system atrophy (n = 7), Parkinson's disease (n = 3), diabetic neuropathy (n = 1), amyloid neuropathy (n = 1), and idiopathic autonomic neuropathy (n = 3). Methods: Heart rate, blood pressure, peripheral resistance index (PRI), cardiac index, stroke index, and end diastolic index were monitored continuously during supine rest and head up tilt before and one hour after an oral dose of 60 mg pyridostigmine. Results: There was only a modest non-significant increase in supine blood pressure and PRI. In contrast, acetylcholinesterase inhibition significantly increased orthostatic blood pressure and PRI and reduced the fall in blood pressure during head up tilt. Orthostatic heart rate was reduced after the treatment. The improvement in orthostatic blood pressure was associated with a significant improvement in orthostatic symptoms. Conclusions: Acetylcholinesterase inhibition appears effective in the treatment of neurogenic orthostatic hypotension. Orthostatic symptoms and orthostatic blood pressure are improved, with only modest effects in the supine position. This novel approach may form an alternative or supplemental tool in the treatment of orthostatic hypotension, specially for patients with a high supine blood pressure.